Peran Polimorfisme Promotor Gen Interleukin-10 pada Penyakit Kusta: Tinjauan Sistematik - Desi Oktariana; Irsan Saleh; Zen Hafy; Iche Andriyani Liberty (Majalah Kedokteran Indonesia, 2023)
Introduction: Leprosy remains a significant problem in Indonesia as the number of cases has not been eliminated until now. One of the cytokines that plays a role in the disease is interleukin-10 (IL-10), which has a dominant anti-inflammatory effect and influences the immunopathogenesis of leprosy. Genetic factors, including the IL-10 gene promoter polymorphism, affect the amount of IL-10 produced, thereby increasing the risk of leprosy. Therefore, the objective of this study is to gather information on the role of IL-10 gene promoter polymorphism in the development of leprosy.Method: A systematic review method was used to identify, evaluate, and extensively discuss published works through national and international journals such as Google Scholar, Science Direct, Elsevier, EBSCO, Medline, PubMed, Proquest, and Wiley. The study was conducted by searching relevant keywords related to the research topic in these databases. Subsequently, article selection was performed based on predetermined inclusion and exclusion criteria. The selected articles were then evaluated for quality to ensure accuracy and reliability of the presented information. Finally, the results of this systematic review were used to obtain accurate and up-todate information regarding the role of IL-10 gene promoter polymorphism in leprosy.Results: This systematic review analyzed a total of 14 articles and revealed that results varied among study populations. However, there is consistent evidence to suggest that the IL-10 gene promoter polymorphism is associated with leprosy, which was found in the majority of the study populations.Conclusion: IL-10 gene promoter polymorphism tends to be associated with leprosy.